Scaling leaf respiration with nitrogen and phosphorus in tropical forests across two continents. Issue 3 (9th May 2016) - Rowland, Lucy; Zaragoza‐Castells, Joana; Bloomfield, Keith J.; Turnbull, Matthew H.; Bonal, Damien; Burban, Benoit; Salinas, Norma; Cosio, Eric; Metcalfe, Daniel J.; Ford, Andrew; Phillips, Oliver L.; Atkin, Owen K.; et al.
Summary: Leaf dark respiration ( R dark ) represents an important component controlling the carbon balance in tropical forests. Here, we test how nitrogen (N) and phosphorus (P) affect R dark and its relationship with photosynthesis using three widely separated tropical forests which differ in soil fertility. R dark was measured on 431 rainforest canopy trees, from 182 species, in French Guiana, Peru and Australia. The variation in R dark was examined in relation to leaf N and P content, leaf structure and maximum photosynthetic rates at ambient and saturating atmospheric CO2 concentration. We found that the site with the lowest fertility (French Guiana) exhibited greater rates of R dark per unit leaf N, P and photosynthesis. The data from Australia, for which there were no phylogenetic overlaps with the samples from the South American sites, yielded the most distinct relationships of R dark with the measured leaf traits. Our data indicate that no single universal scaling relationship accounts for variation in R dark across this large biogeographical space. Variability between sites in the absolute rates of R dark and the R dark : photosynthesis ratio were driven by variations in N‐ and P‐use efficiency, which were related to both taxonomic and environmental variability. Abstract : See also the Commentary on this article by McDowell & Xu, 214 : 903–904 .